Inclusão escolar de alunos com deficiência : interface com os conteúdos da Educação Física - Carvalho, Camila Lopes de; Araújo, Paulo Ferreira de (2018)
Physical Education has been redefined in recent decades, its objectives, aims, contents and performances at school, at the same time, that it has incorporated ideas of inclusion socially established. Thus, the aim of this study is to analyze the process of inclusion of students with disabilities in Physical Education in their main content. Therefore, a qualitative survey was conducted, consisting of a case study, where lessons of physical education in a class of 2nd year of elementary school, which has two students with disabilities, were observed for 1 school year, with data analysis by categorization. A predominance of positive aspects to the inclusion was seen (active participation and positive interactions among all the classes), but intermingled with other negative (Game and Sports over others contents, and negative interactions in competitive and technical activities). In conclusion, there is a positive construction of inclusive physical education at schools but there is a need for more professional training to explore the different contents of Physical Education and associate them to inclusive education.
Nas últimas décadas, a Educação Física brasileira foi redefinida em seus objetivos, finalidades, conteúdos e atuações no cenário escolar, ao mesmo tempo no qual passou a incorporar os ideais inclusivos estabelecidos socialmente. Dessa forma, o objetivo desse estudo foi analisar o processo de inclusão de alunos com deficiência na Educação Física Escolar no contexto brasileiro, perante seus principais conteúdos, conforme estabelecido pelo movimento renovador da área - Dança, Esporte, Ginástica, Jogo e Luta. Para isso, foi realizada uma pesquisa qualitativa, composta por um estudo de caso, no qual as aulas de Educação Física de uma turma do 2° ano do ensino fundamental I, que possuiu dois alunos com deficiência, foram observadas durante 1 ano letivo, com análise de dados por categorização. Foi verificada uma predominância de aspectos positivos à inclusão (maioria de participações ativas e interações positivas entre todos nas aulas), mas entremeados por outros negativos (superioridade de aulas dos conteúdos de Jogo e Esporte sobre os demais, e interações negativas em atividades de caráter competitivo e técnico). Concluindo, tem ocorrido uma construção positiva em direção à Educação Física inclusiva, mas que ainda necessita de maior capacitação docente para explorar os diversos conteúdos desta área durante as aulas, associando-os às práticas de inclusão.
Keywords: Special Education; Inclusive Education; Physical Education; Educação Especial^lpt; Educação Inclusiva; Educação Física Escolar; Personas con discapacidad; Educación; Enseñanza primaria; Brasil